(untitled) (Journal of Hama University, 2022)
This study aimed to analyze the effect of entrepreneurship orientation on the market value of banks, by studying seven dimensions of entrepreneurship which are(risk-taking, pro-activeness, innovations, competitive aggressiveness, autonomy, market orientation and environment).The research was based on the descriptive and analytical approach, whereby an electronic questionnaire was designed are directed to the study sample, which is the Arab Bank, the bank of Syria and the Gulf, and the Bank of Jordan. It reached 239 items, with the aim of measuring their estimate of the effect of the entrepreneurial orientation. The researcher used multiple linear regression and SPSS program to extract the data. The results showed that each of (competitive aggressiveness, autonomy, environment) has a positive and significant effect on Profitability of banks. In contrast, we found that (risk-taking, pro-activeness, innovations and customer-orientation, rival-orientation) had no significant effect on market value of banks. One of the most important recommendations that Banks must adopt the dimensions of the entrepreneurial orientation in their business as the banking industry is a changing and rapidly changing market. In light of the uncertainty and market turmoil, investing in the competitive aggressiveness dimension appears wise by offering lower interest rates than competitors to expand the employment of funds, thus increasing the return on the share and thus increasing the market value of banks.